An investigation into the possible neuroprotective role of melatonin in copper-loading - Parmar, Paresh H (Rhodes University, Faculty of Pharmacy, Pharmacy, 2001)
Copper is an extremely toxic metal in biological systems and thus, its availability to the system, must be effectively and efficiently controlled. Copper is vital for life, as it is essential for critical enzymes in biological systems. It is free copper in the biological systems that is toxic, as free copper induces free radical generation, which disrupts lipid membranes, interacts with DNA causing mutations, and eventually leads to cell death. Wilson's disease is a inherited copper disease, which results in hepatolenticular disease. Copper is unable to be excreted, and thus accumulates, eventually spilling over into the bloodstream from the liver, and "poisons" the patient. The Wilson's disease patient leads a short life, due to neurological and hepatological problems. There is no cure for Wilson's disease, only chelation therapy using potent chelators such as penicillamine and EDTA. Zinc, in high doses, can be used to compete with copper absorption. This has proved to be the only successful therapy at present. This study investigates the possible use of melatonin as a copper binder/chelator. Melatonin has been shown to interact with copper in vitro. By binding/chelating to copper, melatonin may inhibit copper-induced free radical generation, and thus prevent copper from interacting with DNA to cause mutations and act as a cytotoxin. In vivo studies on copper (2mg/kg) administered for 2-weeks and 6-weeks were carried out on Wistar rats. The potential of melatonin (12mg/kg) to prevent copper-induced cellular damage was investigated. The results indicate that melatonin does not protect the lipid membranes from copper-induced lipid peroxidation. In vitro investigations using 1mM, 5mM and 10mM copper and 5mM melatonin, show that melatonin prevents copper-induced lipid peroxidation at a copper concentration of 1mM (p<0.001). The 5mM and 10mM copper induces less lipid peroxidation, compared to the 1mM copper. It has been reported that metal ions, antioxidants and chelating agents can influence peroxide decomposition during the assay. Melatonin (5mM) administration does not significantly prevent copper-induced lipid peroxidation at 5mM and 10mM copper. It is possible that due to melatonin's relatively low concentration, it is unable to inhibit lipid peroxidation induced by the copper. The chemical nature of the interaction between melatonin and copper was also investigated, using NMR, IR and electrochemistry techniques. The NMR and IR techniques show that melatonin coordinates with CuÂ²â º and not CuÂ¹â º, at the carbonyl group of melatonin. The electrochemistry experiments using cyclic voltammetry and adsorptive stripping voltammetry, show that melatonin forms a strong bond with CuÂ¹â º. CuÂ²â º prefers binding to oxygen, and that is clearly seen in the NMR and IR. CuÂ¹â º prefers binding to nitrogen and then oxygen, and this is seen in the electrochemistry, as CuÂ¹â º is forced to bind through one of the nitrogens on the melatonin. Previously, it has been shown that melatonin binds/chelates with CuÂ²â º. Histochemical investigations show that copper administration for 2-weeks and 6-weeks, causes extensive mitochondrial damage in liver and kidney's proximal convoluted tubule epithelium cells. Melatonin (12mg/kg) co-administration with copper for 2-weeks and 6-weeks did not significantly protect the mitochondria from copper-induced damage. Copper-specific stains (rhodanine, silver sulphide and rubeanic acid) were used to stain liver, brain and kidney tissue samples. Rhodanine and silver sulphide were equally sensitive in staining copper in the 2-week samples, but not at all in the 6-week samples. This could not be explained. Rubeanic acid was ineffective in all samples tested. Thus, it appears that specific copper stains cannot be used in making a definitive diagnosis in cases of copper overload, and that specific copper stains do not always correlate with a high concentration of copper present in tissues. Pineal organ culture was used to determine the effect of copper administration on pineal indole synthesis. Exogenous (Â³H) tryptophan was administered to the pineal organ cultures, and the level of (Â³H) pineal indoles synthesised, were measured. Pineals from 2-week and 6-week copper/melatonin treated animals exhibited paradoxical 5- methoxytryptophol (ML) levels, as compared to the 2-week and 6-week copper treated animals. The 2-week copper/melatonin administered animals, showed a decrease in the ML level (p<0.01), and the copper/melatonin administered for 6-weeks, showed an increase in the ML levels (p<0.01). This indicates that melatonin interacts with the HIOMT enzyme. Pineals from 6-week copper/melatonin treated animals, as compared to the 6-week copper treated animals, showed an increase in N-acetylserotonin levels. This indicates that melatonin prevents the inhibition of the NAT enzyme. The final experiment was to determine in vitro, the effect of CuÂ²â º and CuÂ¹â º administration, on mitochondrial electron transport chain. Rat liver homogenate was incubated with and solutions of CuÂ²â º (10mM) and CuÂ¹â º (10mM) and melatonin (10mM). CuÂ²â º administration caused an inhibition of the electron transport at t=0 and t=60, whereas CuÂ¹â º administration at t=0 caused an inhibition of electron transport, but at t=60, CuÂ¹â º administration stimulated electron transport. Melatonin administered with CuÂ²â º, resulted in an inhibition of the electron transport chain at t=0 and t=60. The findings of this study indicate that melatonin might have a potentially beneficial effect in copper overloading, by binding/chelating copper.
Keywords: Melatonin; Copper; Nervous system -- Degeneration -- Treatment